Vasopressinergic Activity of the Suprachiasmatic Nucleus and mRNA Expression of Clock Genes in the Hypothalamus-Pituitary-Gonadal Axis in Female Aging - Nicola, Angela Cristina [UNESP]; Ferreira, Larissa Brazoloto [UNESP]; Mata, Milene Mantovani; Vilhena-Franco, Tatiane; Leite, Cristiane Mota; Martins, Andressa Busetti; Antunes-Rodrigues, José; Poletini, Maristela Oliveira; Dornelles, Rita Cássia Menegati [UNESP] (Frontiers, 2021)
The important involvement of the suprachiasmatic nucleus (SCN) and the activity of vasopressinergic neurons in maintaining the rhythmicity of the female reproductive system depends on the mRNA transcription-translation feedback loops. Therefore, circadian clock function, like most physiological processes, is involved in the events that determine reproductive aging. This study describes the change of mRNA expression of clock genes, Per2, Bmal1, and Rev-erbα, in the hypothalamus-pituitary-gonadal axis (HPG) of female rats with regular cycle (RC) and irregular cycle (IC), and the vasopressinergic neurons activity in the SCN and kisspeptin neurons in the arcuate nucleus (ARC) of these animals. Results for gonadotropins and the cFos/AVP-ir neurons in the SCN of IC were higher, but kisspeptin-ir was minor. Change in the temporal synchrony of the clock system in the HPG axis, during the period prior to the cessation of ovulatory cycles, was identified. The analysis of mRNA for Per2, Bmal1, and Rev-erbα in the reproductive axis of adult female rodents shows that the regularity of the estrous cycle is guaranteed by alternation in the amount of expression of Bmal1 and Per2, and Rev-erbα and Bmal1 between light and dark phases, which ceases to occur and contributes to determining reproductive senescence. These results showed that the desynchronization between the central and peripheral circadian clocks contributes to the irregularity of reproductive events. We suggest that the feedback loops of clock genes on the HPG axis modulate the spontaneous transition from regular to irregular cycle and to acyclicity in female rodents.
Keywords: aging; clock genes; hypothalamus-pituitary-gonadal axis; kisspeptin; suprachiasmatic nucleus; vasopressin